EXPLORING THE CHEMICAL FINGERPRINTS: FOURIER TRANSFORM INFRARED SPECTROSCOPY ANALYSIS OF SELECTED PLANTS USED IN THE TREATMENT OF UROLITHIASIS (International Journal of Food and Nutritional Sciences, 2021)
The functional groups present in plant extracts have been identified using FTIR Spectroscopy, which has been proven to be a reliable and sensitive approach. These functional groups were identified using IR region in the range of 400-4000cm-1. It may be the most important, reliable method for determining the kinds of chemical groups (functional groups) that are present in compounds. The leaf powders of Ouretlanata(L.) Kuntze andTribullusterrestris(L.) were taken for the present study. The predominance of functional groups in the chosen samples, such as amines, alcohols, phenol, carboxylic acids, ethers, and esters, is linked to their therapeutic qualities, particularly the urolithiatic property. It will be further determined with the help of GCMS analysis.